2018
DOI: 10.1007/s00259-018-4117-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lanreotide on uptake of 68Ga-DOTATATE in patients with neuroendocrine tumours: a prospective intra-patient evaluation

Abstract: Lanreotide injection prior to Ga-DOTATATE PET/CT does not result in decreased tumour uptake. In contrast, tumour uptake was increased, whereas the uptake in normal organs is decreased, leading to an increased tumour-to-liver ratio. However, these differences were small and not deemed clinically relevant. These results strongly suggest that discontinuation of lanreotide injections in the weeks prior toGa-DOTATATE PET examinations is unnecessary and does not compromise nuclear medicine imaging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 21 publications
4
50
0
Order By: Relevance
“…The European Association of Nuclear Medicine procedure guidelines for 68 Ga-DOTATATE PET/CT suggest an interval of 3-4 wk after administration of LA SSA to avoid potential somatostatin receptor blockade, although the evidence to support this is scarce (5). Published data rather support an improved tumor-to-background ratio during LA SSA treatment (11)(12)(13)(14). An area where there is even less evidence is the clinical significance of changes in 68 Ga-DOTATATE uptake and how they relate to tumor progression and regression.…”
mentioning
confidence: 99%
“…The European Association of Nuclear Medicine procedure guidelines for 68 Ga-DOTATATE PET/CT suggest an interval of 3-4 wk after administration of LA SSA to avoid potential somatostatin receptor blockade, although the evidence to support this is scarce (5). Published data rather support an improved tumor-to-background ratio during LA SSA treatment (11)(12)(13)(14). An area where there is even less evidence is the clinical significance of changes in 68 Ga-DOTATATE uptake and how they relate to tumor progression and regression.…”
mentioning
confidence: 99%
“…The second point one should address is a possible influence of the SSAs' therapy on the uptake of DOTATATE radiopharmaceutical. Several authors have demonstrated very clearly the benefits of a radiopharmaceutical-DOTApeptide administration when used in conjunction with SSAs (short-or long-acting formulation) [10,13,14]. Regarding the diagnostic procedure, a prior SSAs' administration seems to produce a better image contrast between target lesions and normal tissue, together with a "tumour sink phenomenon" [15] that decreases the [ 177 Lu]DOTApeptide uptake in healthy organs.…”
mentioning
confidence: 99%
“…Aalbersberg et al have recently assessed the influence of Lanreotide administration on the [ 68 Ga]DOTATATE uptake in advanced NET patients, who were treated the previous day with prolonged-release SSAs [14]. In their prospective data, the SSAs injection does not interfere in the [ 68 Ga] DOTApeptide-SSTRs binding.…”
mentioning
confidence: 99%
See 2 more Smart Citations